Intuitive forecasting and analytical reasoning: does investor personality matter?: A multi-method analysis. (17th July 2019) - Misra, Rupali; Srivastava, Sumita; Banwet, Devinder Kumar
Abstract : Purpose: In spite of an intuitive appeal regarding association between personality and investment efficacy, there is a dearth of empirical support for the effects of theoretically meaningful personality difference on intuitive and analytical ability, which further explains investment efficacy. The current study aims to explore this link using multi-method analysis. Design/methodology/approach: In Study 1, the experimental protocol captures intuitive responses of naïve investors in four different investment horizons and maps the findings with personality constituents of the Big Five (Costa and McCrae, 1992), while in Study 2, survey of active investors seeks their preference for intuition or deliberation (PID, Betsch, 2004) in decision-making, along with measuring their investment efficacy and analysing the results on the basis their personality Type A vs Type B. Findings: Subjects with lower extraversion tend to have superior forecasting accuracy for gold and dollar, while those with lower neuroticism have tendency of superior forecasting for dollar and Nifty index in mid-term investment. Further, in Study 2, the results indicate superior intuitive ability, analytical ability and investment efficacy of Type B investors. Originality/value: The study is unique in two ways. One, it explores the role of personality in ambidextrous decision-making framework, where rationality and intuition iteratively operate in a parallel, yet synchronous, fashion. Two, the study attempts to examine the role of personality in the unique socio-cultural context of an emerging economy such as India with Eastern religious traditions, having strong implications on the personal characteristics of the decision agents.